If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1x = x + -4x Combine like terms: 8x + -1x = 7x 7x = x + -4x Combine like terms: x + -4x = -3x 7x = -3x Solving 7x = -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 7x + 3x = -3x + 3x Combine like terms: 7x + 3x = 10x 10x = -3x + 3x Combine like terms: -3x + 3x = 0 10x = 0 Divide each side by '10'. x = 0.0 Simplifying x = 0.0
| v-32t=v | | 5(x-3)+3(x-4)=5x-6 | | 97=11x+3-6x | | 63-2x=14-9x | | Y/8-15_=2 | | 5x/2=18 | | 10(x-2)-8=8x+6 | | 10x+4+2x=103 | | 59-5x=14-10x | | Xsquared-x=17 | | 86=3x-12 | | [-2-3x]+x=9-x | | 5(x-3)+(x-4)=5x-6 | | 2xy+3xy=5xy | | 0.5-0.2=9.3 | | 72/u=8 | | 6x+10=-4-4x | | 4x+3=3+6x-8 | | 5x+8=66 | | 480/y=24 | | 5log^5(9-x)=6 | | 5(x-3)=13x-5 | | 100=10x+5y+0.5z | | 10m-13=57 | | g/8-5=8 | | 1/5x-2=15 | | 2+7x=8+x | | 8(x+3)=2x+66 | | x+1=10-8 | | 10z+4=54 | | 2+10x=-7x | | 6x+15=7x+13 |